O furor no Hércules furioso de Sêneca: estudo e tradução - Vieira, Hermes Orígenes Duarte (2013)
Object of the thesis is analysis of the dramatic representation of the furor in the tragedy of Seneca Hercules furens (furious Hercules). To this end, a study of Roman furor is made in the light of the Stoic understanding of the cognitive and moral nature of human passions. There are four chapters. In the first, "Considerations on the tragic sense in Hercules furens under the stoic bias," a reflection on a possible tragic sense is made for Seneca, a Stoic philosopher. The pain, fury and nefas are also studied as categories of the tragic action of Hercules in the piece in question. In the second chapter, "The ambivalence of Heracles-Hercules," an overview is made of several representations of Hercules in the most diverse literary genres of Greek and Latin authors in order to situate the image of this hero in Greco-Latin literature and influence which Seneca received from this literary tradition. In the third chapter, "Seneca: Between Tragedy and Philosophy," we work on general concepts of Stoicism, such as the themes of Stoic "representation" and "passion" to show how they model the tragedy of Seneca. In the fourth chapter, "Ira and Furor in Hercules Furens" the literary and stoic representation of the furor of Hercules in the mentioned piece is studied. Part of the comparison between the Heracles, of Euripides, and the Hercules, of Seneca to emphasize the singular way of Seneca to structure the dramatic action, the wrath and fury of Hercules. It can be seen that the Hercules of Seneca is the dramatic and literary illustration of the angry man studied and criticized by Seneca in his philosophical works, especially in the work De ira (On the anger)